Improving patients with chronic lower limb arterial ischaemia - Anna Karpińska; Ewa Karpińska (Kazimierz Wielki University, 2019)
Atherosclerosis of the lower limb arteries is the cause of ischemia in their area. Improper supply of nutrients to the leg muscles by blood results in pain, in particular those that intensify during exercise, when the nutritional need increases in the contracting muscles. The task of the physiotherapist is to improve the patient's quality of life. At the beginning, proper diagnostics should be performed to assess the level of ischemia, its severity and the patient's physical abilities. To assess these properties, a 6-minute gait test, ABI index and intermittent claudication distance test can be used. In therapy, special attention should be given to training on the treadmill, cycloergometer, walks and resistance exercises. The basic premise of improvement is to extend the patient's pain-free distance.